The influence of the physigraphic and geologic condition aspects on the environmental degradation in the city of Guaratingueta - Tsutiya, A. M.; Tanaka, A.; Simoes, SJC; Barelli, N.; Kamon, M. (A A Balkema, 1996)
The present paper deals with environmental degradation in the city of Guaratingueta, Brazil; as a result of disordered urban settlement and development. Three site areas in the city resting on different geologic units were selected for the analyses, i.e.: precambrian rocks, tertiary sedimentary basin, and recent quaternary soil deposits. It has been found that geological and geotechnical aspects are fundamental to form the basis for environmental preservation and urban planning.